Marketing Management of The Principal in An Effort to Increase the Number of New Students in Madrasah Aliyah Nurul Iman Singkut - Meri Aulia; Fuad Rahman; Sukarno Sukarno (International Journal of Education and Digital Learning (IJEDL), 2023)
This study aims to analyze the role of school principals in school marketing management in order to increase the number of new students. Principals play an important role in developing effective marketing strategies to attract prospective students and parents. This research will involve school principals, teachers, students, and student guardians as respondents. The research method used is qualitative research. Data collected using observations, interviews and documentation. Meanwhile, data analysis was carried out using data reduction, data presentation, and verification. Efforts made by madrasa heads to increase the number of new students involve several steps, such as market analysis, understanding competition with other educational institutions, financial analysis, forming marketing teams or committees, and implementing marketing strategies through various methods such as promotion through print media, optimizing relations with educational institutions and other institutions, as well as word of mouth promotion. Apart from that, service counters were also made, and information was provided to the public about the absence of registration fees and tuition fees. The process of supervising the implementation of activities is carried out through weekly evaluation meetings and directions to team members and teachers. The results of marketing management carried out by the head of the madrasa show that the community in general feels the presence of Madrasa Aliyah Nurul Iman Singkut and the good contribution it makes to the surrounding environment. The marketing efforts undertaken have also succeeded in improving relations with stakeholders. Even though marketing management has been well implemented, the increase in the number of new students at Madrasah Aliyah Nurul Iman Singkut is still not significant due to certain factors that become obstacles, such as competitors in educational institutions, limited budgets, limited facilities and infrastructure, and limited human Resources. on the other hand.